Cadaver Models in Residency Training for Uncommonly Encountered Ultrasound-Guided Procedures - Richard Amini (Journal of Medical Education and Curricular Development, 2019)
Background: Arthrocentesis of the ankle and elbow and brachial plexus nerve blocks are infrequently performed procedures; however, clinicians in specialties such as emergency medicine are required to be proficient in these procedures in the event of emergent or urgent necessity. Objectives: The objective of this study was to create, implement, and assess a fresh cadaver-based educational model to help resident physicians learn how to perform ultrasound-guided arthrocentesis of the ankle and elbow and ultrasound-guided regional nerve blocks. Methods: This was a single-center cross-sectional study conducted at an academic medical center. After a brief didactic session, 26 emergency medicine residents with varying levels of clinical and ultrasound experience rotated through 4 fresh cadaver-based stations. The objective of each station was to understand the sonographic anatomy and to perform ultrasound-guided arthrocentesis or regional nerve block with hands-on feedback from ultrasound fellows and faculty. Participants were subsequently asked to complete a questionnaire which evaluated participants’ experience level, opinions, and procedural confidence regarding the 4 stations. Results: A total of 26 residents participated in this study. All 26 residents agreed that the cadaver model (compared with clinical anatomy) was realistic regarding ultrasound quality of the joint space, ultrasound quality of the joint effusion, ultrasound quality of nerves, tissue density, needle guidance, and artifacts. Finally, there was a statistically significant difference between mean scores for pre-simulation and post-simulation session participant procedural confidence for all 4 procedures. Conclusions: This fresh cadaver-based ultrasound-guided educational model was an engaging and well-received opportunity for residents to gain proficiency and statistically significant confidence in procedures which are uncommonly performed in clinical settings.